Integrating Disaster Risk Management into Infrastructure Governance: A Framework for Resilient Development in Indonesia - Muhammad Hakiem Sedo Putra; M. Ridho Ulya; Zainal Alim (PT Penjaminan Infrastruktur Indonesia (Persero), 2026)
Indonesia is highly vulnerable to disasters, e.g., floods, landslides, earthquakes, and volcanic eruptions; all of which pose serious risks to public infrastructure resilience. Although infrastructure investment continues to increase, disaster risk considerations are not fully integrated into infrastructure planning and governance. This study develops a conceptual framework for integrating Disaster Risk Management (DRM) into public infrastructure governance in Indonesia. Using secondary data from the National Disaster Management Agency, the Ministry of Public Works and Housing, and international development reports, the study applies a qualitative approach to examine policy frameworks, institutional arrangements, and the use of risk information in infrastructure planning. The findings show that infrastructure governance in Indonesia remains largely reactive, with limited use of hazard mapping in spatial planning and weak coordination among relevant institutions. The proposed framework emphasizes cross-sectoral coordination, systematic use of geospatial risk data, and community participation in planning and decision-making. Strengthening these mechanisms can enhance infrastructure resilience, reduce disaster-related losses, and support sustainable public infrastructure investment.